The structure of uncertainty in future low carbon pathways - Hughes,N; Strachan,N; Gross,R (Energy Policy, 2013)
Low carbon scenario and transition pathway analysis involves the consideration of uncertainties around future technological and social changes. This paper argues that uncertainty can be better understood, and the strategic and policy effectiveness of scenarios or pathways thereby improved, through a systematic categorisation of the different kinds of certain and uncertain elements of which the future is comprised. To achieve this, this paper makes two novel methodological contributions. First it proposes a system conceptualisation which is based on a detailed description of the dynamics of the actors and institutions relevant to the system under study, iteratively linked to a detailed representation of the technological system. Second, it argues that as a result of developing this actor-based low carbon scenarios approach it is possible to characterise future elements of the system as either pre-determined, actor contingent or non-actor contingent. An outline scenario approach is presented, based on these two contributions. It emerges that the different categories of future element are associated with different types of uncertainty and each prompt different strategic policy responses. This categorisation of future elements therefore clarifies the relationship of scenario content to specific types of policy response, and thus improves the policy tractability of resulting scenarios.